Kajian Manfaat Implementasi Program Pamsimas di Desa Pekuncen, Kecamatan Pegandon, Kabupaten Kendal - Kemala Yasmine; Mardwi Rahdriawan (Jurusan Perencanaan Wilayah dan Kota, 2020)
Pekuncen Village is one of the villages in Kendal Regency that implements a Community-Based Water and Sanitation Program called the Pamsimas which has been running for two years. During this period, there was no doubt a change in water supply before and after the existence of its. This study aims to determine the benefits of implementing the Pamsimas program in Pekuncen Village. The method used is a quantitative method with data collection techniques through questionnaires to all Pamsimas recipient communities in this village, as many as 115 respondents. Besides, interviews also conducted with the clean water manager in this research area. The analysis technique used is descriptive analysis, with a breakdown of the data obtained using a frequency distribution. The results of this study indicate that after the implementation of the Pamsimas program in Pekuncen Village has positive impacts and benefits for the local community. The effect is in the form of increasing community participation, increasing access to clean water in cities: improving public health figures and organizing the program in an organized manner.